Representations and imaginaries of cities in the opening sequences of three U.S. TV series: The Sopranos, Weeds and House of Cards - Marta Gallardo; David García-Reyes (Boletín de la Asociación de Geógrafos Españoles)
Representaciones e imaginarios urbanos a través de los opening de tres series estadounidenses: The Sopranos, Weeds y House of Cards